1997
DOI: 10.1076/ceyr.16.8.782.8982
|View full text |Cite
|
Sign up to set email alerts
|

Human T-cell lymphotropic virus type 1 can infect primary rat retinal glial cells and induce gene expression of inflammatory cytokines

Abstract: These results provided supportive evidence for the theory that the infection of retinal glial cells by HTLV-1 and subsequent production of inflammatory cytokines could be one contributing factor for the development of the unique clinical features of HU. A better understanding of the specific roles of the inflammatory cytokines in the pathogenesis of HU would be beneficial in the treatment and control of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…11) It was also reported that the supernatant of irradiated MT-2 cells contained about 250 pg/ml of HTLV-1 p19 antigen. 36) The virus preparation from c77 cells used in this study contained about 100 times more p19 antigen than the reported MT-2 cell culture supernatant. Mouse cell lines used previously are mostly fibroblasts, LMTK− and LMTK− derived mouse/human hybrid cells.…”
Section: Discussionmentioning
confidence: 71%
“…11) It was also reported that the supernatant of irradiated MT-2 cells contained about 250 pg/ml of HTLV-1 p19 antigen. 36) The virus preparation from c77 cells used in this study contained about 100 times more p19 antigen than the reported MT-2 cell culture supernatant. Mouse cell lines used previously are mostly fibroblasts, LMTK− and LMTK− derived mouse/human hybrid cells.…”
Section: Discussionmentioning
confidence: 71%
“…The proviral copy numbers showed a gradual decrease after infection. This transient infection was noted in retinal glial cells [ 19 ]. The possibility that HTLV-I-infected lung epithelial cells do not produce a large amount of virus and show a slower growth rate was raised by a report of Sato et al [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the tropism of HTLV-I for lung epithelial cells. Because HTLV-I exhibits tropism for synoviocytes, thyrocytes and retinal glial cells [ 17 - 19 ], we sought to determine whether lung epithelial cells can be infected with HTLV-I and whether such infection modulates the expression of cellular genes.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several studies have shown that astrocytes can be infected by HTLV-1 both in vivo and in vitro (23,24,28). An increased secretion of cytokines, such as granulocyte-macrophage colony-stimulating factor and TNF-␣, by HTLV-1-infected glial cells appears to be responsible for an increased expression of matrix metalloproteinases (MMPs) 3 and 9 and of tissue inhibitor of metalloproteinase 3 by these cells (6,28,37). In addition, a recent study detected MMP-9 in the cerebrospinal fluid of HTLV-1-infected patients with TSP/HAM (7).…”
Section: Discussionmentioning
confidence: 99%